Strategic Management of PPIQ Tahsin in Meeting The Needs of Mu'allim in Islamic Boarding School - Moch. Rizwan Aprilianto; Moh. Rofiki; Eka Diana (Mudir : Jurnal Manajemen Pendidikan, 2024)
Abstract: This research discusses the implementation of strategic management used by PPIQ Tahsin in meeting the needs of mu’allim at Nurul Jadid Islamic Boarding School. The low level of reading al-Qur'an among students is due to a lack of teachers, or mu’allim. The research approach uses qualitative methods for the type of case study. The object of the research is the Qur'an education center of Nurul Jadid Islamic Boarding School. The research data collection technique consists of participant observation, in-depth interviews, and documentation studies. The research data consists of primary and secondary data, where primary data is obtained through observation and interviews with five informants consisting of the director and secretary of the al-Qur'an Science Education Center (PPIQ), the head of the Nurul Jadid mu'allim section, the boarding bureau, and the head of the tahsin section. Secondary data were obtained from national and international journals that are in accordance with the research topic. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The results showed that first, PPIQ Tahsin's strategy formulation is based on objectives with internal and external environmental analysis. Second, the implementation of the PPIQ Tahsin strategy is carried out in a structured and efficient manner. This is reflected in the activity program and the education system that support producing mu'allim al-Qur'an. Third, strategy evaluation at the PPIQ Tahsin dormitory is carried out regularly every three months. Program evaluation includes rigorous exams, such as tajweed written exams, memorization exams involving recitals of verses selected by the examiner, and al-Qur'an recitation exams assessed by the examiner.